(untitled) (Journal of Medicine, 2012)
Polycythaemia vera is difficult disease to diagnose when it has an atypical presentation. Here we present a case where a middle aged man who presented to us with abdominal pain and recurrent peptic ulceration and was later diagnosed as a case of polycythaemia vera. To best of our knowledge this is the first report of such association from Bangladesh. DOI: http://dx.doi.org/10.3329/jom.v13i2.12774 J Medicine 2012; 13 : 252-255